2018
DOI: 10.1080/17482631.2018.1474673
|View full text |Cite
|
Sign up to set email alerts
|

Encountering existential loneliness among older people: perspectives of health care professionals

Abstract: Purpose: Existential loneliness is part of being human that is little understood in health care, but, to provide good care to their older patients, professionals need to be able to meet their existential concerns. The aim of this study was to explore health care professionals’ experiences of their encounters with older people they perceive to experience existential loneliness. Method: We conducted 11 focus groups with 61 health professionals working in home care, nursing home care, palliative care, primary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 37 publications
6
70
0
3
Order By: Relevance
“…China has gradually entered the old age society (Qualter, Hurley, Eccles et al, 2018). According to the China Senior Social Followup Report, at least 24.78% of the elderly in the country have a sense of loneliness and 1.40% of the elderly have a serious sense of loneliness (Sundström, Edberg, Rämgård et al, 2018). Moreover, the proportion of people who are living alone in the elderly is more than 5.12%.…”
Section: Introductionmentioning
confidence: 99%
“…China has gradually entered the old age society (Qualter, Hurley, Eccles et al, 2018). According to the China Senior Social Followup Report, at least 24.78% of the elderly in the country have a sense of loneliness and 1.40% of the elderly have a serious sense of loneliness (Sundström, Edberg, Rämgård et al, 2018). Moreover, the proportion of people who are living alone in the elderly is more than 5.12%.…”
Section: Introductionmentioning
confidence: 99%
“…It is not always easy, however, for nurses to discover and be attentive to spiritual and existential concerns, as this requires both parties to be willing to share space (Minton, Isaacson, Varilek, Stadick, & O'Connell‐Persaud, ; Tornøe, Danbolt, Kvigne, & Sørlie, ). A qualitative study by Sundström et al () showed that healthcare professionals experienced different barriers in their encounters with older people's existential loneliness that were related to their own feelings of insecurity and fear, to their abilities and possibilities, and to the concerns of the older person. There are certainly other aspects and factors that hinder or facilitate professionals in addressing existential loneliness, and these may differ among care contexts.…”
Section: Introductionmentioning
confidence: 99%
“…However, this loneliness these older adults experience may be more than having the difficulty with expressing the feelings of loneliness or the loss of social roles or the shrinkage of one's social network, as common examined in the loneliness literature [12][13][14]. Rather, it may stem from the intolerable emptiness and lack of meaningful existence attributed to all the losses they have experienced (i.e., existential loneliness (EL)) [15][16]. Because EL has been linked to serious psychological outcomes (e.g., suicidal ideation [17]), every effort should be made to better understand EL and provide effective psychosocial support of those who experience it.…”
mentioning
confidence: 99%